GnRH agonists in the treatment of symptomatic endometriosis: a reviewEssential Points - Eric S. Surrey, M.D. (F&S Reports, 2023)
The development of highly potent gonadotropin-releasing hormone agonists (GnRHa) allowed for a significant addition to options for the medical management of symptomatic endometriosis. Pituitary GnRH receptor down-regulation leads to a hypogonadotropic and secondary hypoestrogenic state resulting in lesion regression and symptom improvement. There may be an additional effect of these agents on the inflammatory processes associated with endometriosis as well. This is a review of critical milestones in the clinical application of these agents.Most initial trials of various GnRHa employed danazol as a control and demonstrated general equivalence in reducing symptoms and extent of lesions but without hyperandrogenic side effects and adverse metabolic changes induced by the latter. Short-acting GnRHa is administered intranasally or subcutaneously. Longer-acting preparations are administered intramuscularly or as subcutaneous implants. GnRHa also decrease symptom recurrence rates after surgical management. The hypoestrogenic side effects, including bone mineral density loss and vasomotor symptoms, have limited the duration of use of these agents alone to six months. The use of an appropriate add-back allows for the mitigation of side effects while maintaining efficacy and allowing extension of use for up to 12 months. There is a limited amount of data regarding the use of GnRHa in adolescents out of concern for the effect on developing bone. These agents should be used with caution in this group. The lack of dose flexibility, need for parental administration, and side effect profiles represent drawbacks to GnRHa use. The development of oral GnRH antagonists with short half-lives, variable dosing, and decreased side effects represents an exciting alternative.